Motivasi dan Bentuk-Bentuk Partisipasi Umat Katolik dalam Mewujudkan Bonum Commune - Wilfridus Jefrianus Donggo; Nikolaus Anggal (Gaudium Vestrum - Jurnal Kateketik Pastoral, 2019)
This study aims to find the motivation and form of participation of Catholics in an effort to realize the bonum commune. This research is a qualitative descriptive study, to find, analyze, describe, and describe the activities carried out by Catholics in the Church, community, and in relation to other religions (Islam and Christianity) together or based on personal initiative to realize the bonum commune. The characteristics of the informants were categorized according to the status and age of the people. The results showed the existence of the motivation of the people with the categories of instrumental rational action, value rational action, affective action, and traditional action. Meanwhile, the form of community participation is in the form of participation in the form of money, participation in the form of assets, participation in the form of energy, participation in the form of skills, and participation in the form of thoughts.